Microstructure and mechanical properties of powder metallurgy sinter hardening steels with low Cr content - YANG Jie; LIU Le; HUANG Xiaolin (Fenmo yejin jishu, 2023)
Sinter hardening is an established cost-effective process to produce high strength powder metallurgy parts by controlling the cooling speed to affect the sintered microstructure (martensite content) to improve the final performance. A newly developed pre-alloy sinter hardening steels with low Cr content (AstaloyTM CrA) was introduced in this paper, the mechanical properties and microstructure under the different sintering temperature and cooling rate were investigated, and the common powder metallurgy sinter hardening material (Distaloy® DH) was referenced for the comparison. In the results, under the pressing density of 7.0 g·cm−3 at the same carbon level, the AstaloyTM CrA added with 2% nickel (mass fraction) has the highest hardenability which can obtain the highest martensite content and the macro hardness compared to the other materials. AstaloyTM CrA sintered at 1250 ℃ and followed with the cooling rate of 3 ℃·s−1 can achieve the hardness of HRC 38, which can obtain the optimum strength and toughness by sintered at the same temperature and followed with the lower cooling rate of 1 ℃·s−1.